Rotation Station and Learning Motivation: Effects on Job Application Letter Writing Skills in Indonesian Senior High Schools - Yeni Afdal; Syahrul Ramadhan; Ahmad Johari Sihes; Norliza Jamaluddin (AL-ISHLAH: Jurnal Pendidikan, 2025)
Effective job application letter writing is a crucial functional skill for high school students. However, traditional instructional methods often fail to engage learners actively. This study explores the impact of the Rotation Station method—an active learning model adapted from STEM education—on students’ job application letter writing skills, with particular focus on the moderating role of learning motivation. A quasi-experimental design was conducted with 89 Grade XII students at SMA Negeri 20 Batam. Participants were assigned to an experimental group (n = 47), taught using the Rotation Station method, and a control group (n = 42), taught using conventional methods. Writing performance was assessed through a validated test scored with an analytic rubric, and learning motivation was measured using a questionnaire (Cronbach’s α = 0.87). Students were categorized into high- and low-motivation groups based on a median split. Data were analyzed using independent samples t-tests and two-way ANOVA. Students taught using Rotation Station significantly outperformed those in the control group in writing scores (M = 85.64 vs. M = 78.27), t(87) = 4.31, p 0.001. Both high- and low-motivation students benefited similarly, with no significant interaction between teaching method and motivation, F(1, 85) = 1.15, p = 0.286. The Rotation Station method improved writing performance regardless of motivation level, highlighting its potential as an inclusive and effective instructional strategy. Its application in language education supports active engagement and real-world writing practice, offering a valuable alternative to traditional teaching approaches.